2007
DOI: 10.1177/105268460701700301
|View full text |Cite
|
Sign up to set email alerts
|

Horton, Highlander, and Leadership Education: Lessons for Preparing Educational Leaders for Social Justice

Abstract: Influenced by Myles Horton's vision and leadership, the Highlander Folk School became an adult education program centered on social change via the labor and civil rights movements. In this article, I examine the pedagogy and practice of Myles Horton and the Highlander Folk School and identify the key themes that guided their educational approach to social justice leadership training. I then explore the ways in which educational leadership preparation may exemplify these key themes in its pedagogy and practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…As criticisms for schools of education continue due to a perceived lack of academic rigor, program redesign has been recommended as one possible reaction. In a redesign, a program focus on effective programs with well-established academic excellence can lead to the development of a program with the qualities and content educational leaders need supporting a host of research (Andrews & Grogan, 2005;Evans, 2007;Levine, 2005;Maranto et al, 2010;Perry, 2012;Shulman, 2005;Shulman et al, 2006). This intentional redesign may be what doctoral programs need to be effective in preparing scholarly practitioners who can apply theory to practice and achieve educational change by disseminating sound work to key constituents, such as the university, educational institutions, and the community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As criticisms for schools of education continue due to a perceived lack of academic rigor, program redesign has been recommended as one possible reaction. In a redesign, a program focus on effective programs with well-established academic excellence can lead to the development of a program with the qualities and content educational leaders need supporting a host of research (Andrews & Grogan, 2005;Evans, 2007;Levine, 2005;Maranto et al, 2010;Perry, 2012;Shulman, 2005;Shulman et al, 2006). This intentional redesign may be what doctoral programs need to be effective in preparing scholarly practitioners who can apply theory to practice and achieve educational change by disseminating sound work to key constituents, such as the university, educational institutions, and the community.…”
Section: Discussionmentioning
confidence: 99%
“…In the years since Levine's (2005) scathing critique regarding the demise of the Ed.D., educational leadership professors across the country have been challenged to reimagine and redesign Ed.D. programs, in which the focus is on developing the knowledge and skills doctoral students need to serve as effective educational leaders to ensure school improvement (Andrews & Grogan, 2005;Evans, 2007;Perry, 2012;Shulman, 2005;Shulman et al, 2006). Schools of education, specifically doctoral programs in educational leadership, have been criticized for lack of sufficient academic rigor and have received recommendations calling for redesign and reform (Maranto, Ritter, & Levine, 2010;Zirkel, 2012).…”
Section: Educational Leadership Preparation Program Redesignmentioning
confidence: 99%
“…They were facing a reality that they had never lived and for which they were not prepared. Evans (2007) concluded that educational leaders have a social and moral obligation to confront inequitable practices and create more equitable processes and outcomes for students of different racial, socio-economic, gender, and cultural groups. Palacín (2008: 700) states that teachers invest all their energies in order to work coherently and effectively in such a complex context, but the working methodologies that they usually use are not always effective in the new reality.…”
Section: Resultsmentioning
confidence: 99%
“…Levy and Seidel (2006) reflect this sentiment by stating that 'social justice embodies the vision of a society that is equitable and in which all members are physically and psychologically safe' (p. 8). Evans (2007) observed that 'social justice supports the notion that educational leaders have a social and moral obligation to foster equitable school practices, processes, and outcomes for learners of different racial, socioeconomic, gender, cultural, disability, and sexual orientations backgrounds' (p. 250). Dantley (2003) takes this idea further by offering a vision of social justice leaders as purpose-driven leaders who work against an oppressive schooling practices that physically and symbolically violate historically marginalized individuals.…”
Section: Advocacy Social Justice and Competing Theories Of Leadershipmentioning
confidence: 87%